Building Blocks for a Sustainable Future : A Selected Review of Environment and Natural Resource Management in the Republic of Belarus - World Bank (World Bank, Washington, DC, 2020)
The purpose of this review of environmental and natural resource management in Belarus is to highlight how environmental management can contribute to a sustainable future for the country. The report summarizes major macroeconomic trends and associated environmental linkages, environmental trends, and institutional issues facing Belarus in its management of the environment. An extensive analysis of environmental aspects of energy efficiency in Belarus and the state of the water supply and sanitation sector is undertaken. Special attention is given to exploring the environmental impact of the Chernobyl accident and to suggesting additional ways to mitigate lasting radioactive contamination. Natural resource management issues, particularly relating to agriculture, forestry and biodiversity, are also examined.